- #1

- 1,291

- 0

I need help solving these two equations simultaneously

[itex] y = c_1e^{r_1t_o}+c_2e^{r_2t_o}[/itex]

[itex]y' = c_1r_1e^{r_1t_o}+c_2r_2e^{r_2t_o}[/itex] My plan of solving these two equations is by substitution. By rearranging I obtain the following:

[itex]c_1 = [y-c_2e^{r_2t_o}]e^{-r_1t_o}[/itex]

[itex]c_1= \frac{[y' -c_2r_2e^{r_2t_o}]e^{-r_1t_o}}{r_1}[/itex]

Likewise,

[itex]c_2=[y-C_1e^{r_1t_o}]e^{-r_2t_o}[/itex]

[itex]c_2=\frac{[y'-c_1r_1e^{r_1e^r_1t_o}]e^{-r_2t_o}}{r_2}[/itex]

Don't know what to do from here.

[itex] y = c_1e^{r_1t_o}+c_2e^{r_2t_o}[/itex]

[itex]y' = c_1r_1e^{r_1t_o}+c_2r_2e^{r_2t_o}[/itex] My plan of solving these two equations is by substitution. By rearranging I obtain the following:

[itex]c_1 = [y-c_2e^{r_2t_o}]e^{-r_1t_o}[/itex]

[itex]c_1= \frac{[y' -c_2r_2e^{r_2t_o}]e^{-r_1t_o}}{r_1}[/itex]

Likewise,

[itex]c_2=[y-C_1e^{r_1t_o}]e^{-r_2t_o}[/itex]

[itex]c_2=\frac{[y'-c_1r_1e^{r_1e^r_1t_o}]e^{-r_2t_o}}{r_2}[/itex]

Don't know what to do from here.

Last edited: